Formulation and Stability Test of Herbal Cosmetic Preparations of Aloe Vera Body Lotion to Increase Competitiveness of Pharmapreneurs - Herdianty, Juvita; Wijayanto, Arif (Open Access Health Scientific Journal, 2023)
Background: In recent years, the herbal cosmetic industry has experienced significant growth along with increasing public awareness of the importance of natural and environmentally friendly products. Herbal cosmetics not only offer beauty benefits but also provide added value for skin health. However, the main challenge faced by pharmapreneurs is how to ensure the stability and effectiveness of the products they offer in a competitive market.This study aimed to formulate and test the stability of herbal cosmetic preparations, and evaluate their impact on market competitiveness. By understanding the factors that affect product stability, pharmapreneurs are expected to be able to improve the quality and attractiveness of their products.Methods: This study was conducted by formulating several herbal cosmetic preparations, including creams and serums, using natural ingredients such as aloe vera extract, jojoba oil, and essential oils. Stability tests were carried out using storage methods at varying temperatures and humidity, as well as organoleptic tests and periodic pH measurements. The data obtained were analyzed using descriptive statistics to determine changes that occurred during the testing period.Results: The results showed that the formulated herbal cosmetic preparations had good stability, with minimal changes in pH and organoleptic characteristics during the testing period.Conclusion: Product shows potential to compete in the market, with positive feedback from consumers in terms of effectiveness and safety of use.